Antilisterial and Antimicrobial Effect of Salvia officinalis Essential Oil in Beef Sous-Vide Meat during Storage - Gál, Robert; Čmiková, Natália; Prokopová, Aneta; Kačániová, Miroslava (Foods, 2023)
If food is contaminated with pathogens such as Listeria monocytogenes, improper cooking during sous-vide preparation can lead to foodborne illnesses. In this study, it was found that L. monocytogenes were inactivated with both heat and the essential oil of Salvia officinalis (sage EO) in beef tenderloin of the musculus psoas major that had undergone sous-vide processing. To determine whether the enhancement of the efficacy of heat treatment is prospective, L. monocytogenes and sage EO were mixed. Groups with L. monocytogenes alone and sage essential oil combined with L. monocytogenes and test groups without EO were established. The samples were vacuum-packed, inoculated with L. monocytogenes, and then cooked sous-vide for the predetermined duration at 50, 55, 60, or 65 °C. In both groups with sous-vide beef tenderloin, the total bacterial count, the coliforms bacterial count, and the amount of L. monocytogenes were assessed on days 0, 3, 6, 9, and 12. Over these days, the amounts of L. monocytogenes, coliform bacteria, and overall bacteria increased. The identification of bacterial strains in various days and categories was performed by MALDI-TOF mass spectrometry. The test group that was exposed to a temperature of 50 °C for 5 min had a higher overall bacterial count for each day that was assessed. Pseudomonas fragi and L. monocytogenes were the most isolated organisms from the test group and the treated group. To ensure the safety for the consumption of sous-vide beef tenderloin, it was found that the addition of natural antimicrobials could produce effective outcomes.